Analisis Faktor-Faktor Yang Mempengaruhi Konsumen Terhadap Keputusan Pembelian Roti Ketawa Pada Pabrik Roti Ketawa di Kecamatan Bajenis - Sinurat, Yenni Mariani; Br. Saragih, Anju Nindha Andira; Larasati, Intan (Sekolah Tinggi Ilmu Ekonomi Bina karya, 2024)
This study aims to analyze the factors that influence consumers in making purchasing decisions for Roti Ketawa produced by the Roti Ketawa Factory in Bajenis District. The independent variables in this study include brand image, product quality, and price, while the dependent variable is consumer purchasing decisions. Data was collected through a survey using a questionnaire of consumers selected by accidental sampling. The analysis method used is multiple linear regression to identify the partial and simultaneous effects of the independent variables on the dependent variable. The results showed that brand image, product quality, and price partially and simultaneously had a significant effect on purchasing decisions. Among these variables, product quality has a dominant influence in shaping consumer decisions. This study provides recommendations for businesses to continue to improve product quality and build a positive brand image. In addition, competitive pricing also needs to be considered to increase competitiveness in the market. This research is expected to be the basis for developing more effective marketing strategies in the traditional food industry in Tebing Tinggi City.